Glaucoma - structural imagery: HRT, GDX, OCT - Renard, J-P; Giraud, J-M (Journal francais d'ophtalmologie, 2006)
Confocal scanning laser tomography (HRT), scanning laser polarimetry (GDx VCC), and optical coherence tomography provide quantitative data of the retinal fiber layer and optic nerve head. They have become good complementary evaluation tools for glaucomatous optic neuropathy and their results should be analyzed with clinical data. Good knowledge of the parameters they analyze and their limitations are indispensable. To monitor progression of structural involvement, the analysis programs used need to be validated with prospective clinical studies.